Treatment of severe refractory erythema nodosum leprosum with tumor necrosis factor inhibitor Etanercept. Issue 2 (June 2016) - Chowdhry, Sundeep; Shukla, Akhilesh; D'souza, Paschal; Dhali, Tapan; Jaiswal, Prashansa
Abstract: Erythema nodosum leprosum (ENL) is a common complication of lepromatous leprosy. Some patients unresponsive to conventional, first-line therapeutics develop recurrent, recalcitrant ENL. Here, we report a case of severe refractory ENL that was successfully treated with Etanercept. Biologics may be considered as therapeutic alternatives in management of severe, recalcitrant ENL.